Genomic Signature of the Natural Oncolytic Herpes Simplex Virus HF10 and Its Therapeutic Role in Preclinical and Clinical Trials - Eissa, Ibrahim Ragab; Naoe, Yoshinori; Bustos-Villalobos, Itzel; Ichinose, Toru; Tanaka, Maki; Zhiwen, Wu; Mukoyama, Nobuaki; Morimoto, Taishi; Miyajima, Noriyuki; Hitoki, Hasegawa; Sumigama, Seiji; Aleksic, Branko; et al. (Frontiers in Oncology, 2017)
Oncolytic viruses are opening new possibilities in cancer therapy with their unique mechanism of selective replication within tumor cells and triggering of anti-tumor immune responses. HF10 is an oncolytic herpes simplex virus-1 (HSV-1) with a unique genomic structure that has non-engineered deletions and insertions accompanied by frame shift mutations, in contrast to the majority of engineered oncolytic viruses. At the genetic level, HF10 naturally lacks the expression of UL43, UL49.5, UL55, UL56, and latency-associated transcripts, and overexpresses UL53 and UL54. In preclinical studies, HF10 replicated efficiently within tumor cells with extensive cytolytic effects and induced increased numbers of activated CD4+ and CD8+ T cells and natural killer cells within the tumor, leading to a significant reduction in tumor growth and prolonged survival rates. Investigator-initiated clinical studies of HF10 have been completed in recurrent breast carcinoma, head and neck cancer, and unresectable pancreatic cancer in Japan. Phase I trials were subsequently completed in refractory superficial cancers and melanoma in the United States. HF10 has been demonstrated to have a high safety margin with low frequency of adverse effects in all treated patients. Interestingly, HF10 antigens were detected in pancreatic carcinoma over 300 days after treatment with infiltration of CD4+ and CD8+ T cells, which enhanced the immune response. To date, preliminary results from a Phase II trial have indicated that HF10 in combination with ipilimumab (anti–CTLA-4) is safe and well tolerated, with high anti-tumor efficacy. Improvement of the effect of ipilimumab was observed in patients with stage IIIb, IIIc, or IV unresectable or metastatic melanoma. This review provides a concise description of the genomic functional organization of HF10 compared with talimogene laherparepvec. Furthermore, this review focuses on HF10 in cancer treatment as monotherapy as well as in combination therapy through a concise description of all preclinical and clinical data. In addition, we will address approaches for future directions in HF10 studies as cancer therapy.